Treatment of Anterior Crossbite with Skeletal Class III Malocclusion during the Growth Period - Tita Ratya Utari (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2022)
Anterior crossbite is the most common problem in Angle class III malocclusion and is aesthetically disturbing. As individuals get older, an anterior crossbite can worsen, impacting the esthetics of the face and the stomatognathic system’s function significantly and requiring immediate treatment. Due to genetics, habitual postures, ethnicity, and environmental variables, the class III malocclusion’s etiology is multifaceted. In terms of treatment, there are three options: growth modification, camouflage, and orthognathic surgical treatment. This case report aims to describe a non-surgical treatment with simple treatment mechanics in two patients who were still in their growth period. Two patients, a sibling aged 14 and 13 years, experienced an anterior crossbite with a deep overbite, diagnosed with Angle class III with skeletal class III relationships. Besides, the profile revealed a concave, with an overjet of -2mm and an overbite of 4mm. The treatments were then performed employing fixed orthodontic appliances with vertical U-loops for protraction of upper anterior teeth and class III intermaxillary elastics to correct molar relationships. The treatment was completed in two years, in which the anterior crossbite was corrected. The molar and canine relationships, which were originally class III, became class I. Loss of tooth 36 was closed, and tooth 38 has fully erupted. Treatment of anterior crossbite needed to be done as soon as possible to prevent more severe abnormalities. In conclusion, a treatment in the growth period with simple techniques resulted in significant improvements in function and aesthetics.